Guidance and Counseling Teachers’ Strategies in Enhancing Students’ Self-Efficacy at SMAN 3 Lubuk Basung - Marsusi, Mira Eka; I, Irman (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Self-efficacy is an important psychological aspect that influences students’ ability to cope with academic demands, social challenges, and future planning. At the senior high school level, students are faced with various challenges that require strong self-confidence in order to make independent and responsible decisions. This study aims to describe students’ self-efficacy levels, analyze the strategies employed by Guidance and Counseling (GC) teachers to enhance students’ self-efficacy, and identify the supporting and inhibiting factors in the implementation of these strategies at SMAN 3 Lubuk Basung. This research adopts a qualitative approach with a descriptive qualitative design. Data were collected through in-depth interviews, observations, and document analysis involving GC teachers, homeroom teachers, and students. Data validity was ensured through source and technique triangulation as well as member checking. The results indicate that GC teachers implement various services, such as individual counseling, group counseling, and information services focusing on strengthening students’ potential and self-confidence. The strategies applied include providing motivation, positive reinforcement, utilizing students’ successful experiences, and encouraging self-reflection. Supporting factors include school support and GC teachers’ competence, while inhibiting factors include limited service time, a large number of students, and low awareness among some students in utilizing counseling services.